ASYMMETRY AT LANGUAGE LEVELS (Scientific journal of the Fergana State University, 2024)
The article analyzes the imbalances that occur at language levels. With morphemics of disparity; with lexicology and word formation; with syntax and syntax; with syntax and semantics; relationship with semantics and semiotics is studied. In addition, morphological forms have been analyzed for their disproportion to meaning, disproportion to function, disproportion to situation, disproportion to abstraction (uncertainty), and disproportion to signs. It has been proven that the disproportion with respect to characters can be felt in a language itself.